GAME TECHNOLOGIES AND THEIR USE IN PRIMARY EDUCATION (World Bulletin of Social Sciences, 2024)
This article describes the problems of increasing the effectiveness of education in the educational process of primary school and the pedagogical features of their solutions, as well as the role and importance of game technologies in education. Also, the effective introduction of advanced pedagogical technologies and their rational use in primary classes were discussed
Keywords: Pedagogical technology; game technology in education; skill